SIMULATION AND GAME LEARNING AS A MEANS OF DEVELOPING STUDENTS 'COMMUNICATIVE SKILLS (Pedagogy of Higher and Secondary Education, 2009)
In article problems of game training of students are considered with the purpose of development of communicative skills on occupations on foreign language.